Facile synthesis of PdSnCo/nitrogen-doped reduced graphene as a highly active catalyst for lithium-air batteries. (20th February 2017) - Ren, Xiangzhong; Liao, Biyan; Li, Yongliang; Zhang, Peixin; Deng, Libo; Gao, Yuan
Abstract: Well-dispersed trimetallic-alloyed PdSnCo nanocrystals with an average size of 7 nm are supported on nitrogen-doped reduced graphene (NG) nanosheets by a solvothermal method. The PdSnCo/NG nanocatalyst is characterized by scanning electron microscopy, energy dispersive spectroscopy, transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. As a result, the PdSnCo/NG exhibits high catalytic activity toward oxygen reduction reaction and high electrochemical stability in alkaline medium, compared to commercial 10% Pd black, binary PdSn/NG, and PdCo/NG. Moreover, PdSnCo/NG nanocatalyst shows high discharge capacity of 6750 mAh g −1, low charge voltage and predominant cycleability for lithium-air batteries.